Making a speech at the unveiling of a memorial to K. Marx and F. Engels in Voskresenskaya Square (now Revolution Square) in Moscow. Compare: 69/39 A, page 98-99
Making a speech at the unveiling of a memorial to K. Marx and F. Engels in Voskresenskaya Square (now Revolution Square) in Moscow. Compare: 69/39 A, page 98-99.